Yeast Viability in HLD–NAC-Designed Fully Dilutable Lecithin-Linker Microemulsions - Juan Doratt Mendoza; Jingwen Ding; Michelle Acosta Alvarez; Edgar Acosta (Molecules)
Using microemulsions (µEs) as preservation media for cells was pursued in the 1990s; however, the difficulty in formulating biocompatible µEs and keeping unacclimatized cells alive for more than three days hindered developments in this area. This work explores the use of fully dilutable self-microemulsifying delivery systems (SMEDS) formulated with lecithin (Le) and polyglycerol-10-caprylate (PG10C) at a ratio of 2/5. This surfactant blend was mixed with ethyl oleate (EOL) at a ratio of 60 surfactant/40 EOL to produce a D60 dilution line. This D60 SMEDS was diluted with 0.9% w/v NaCl solution to produce lecithin-linker µEs (LLMs). The properties of the resulting LLMs were predicted using the hydrophilic–lipophilic-difference (HLD) and net-average curvature (NAC) model, indicating that LLMs with aqueous content from 5% to 60% are bicontinuous, confirmed via viscosity and conductivity. The largest yeast activity and viability obtained with LLMs were achieved with 30% aqueous content, resulting from the balance between having enough water for the effective transport of metabolites, enough SMEDS to contribute nutrients and lipids, and a low enough water to limit the partition of PG10C that, when present in the aqueous phase, inhibited yeast activity. For SMEDS, its low water activity ensured that the yeast remained dormant, keeping them alive for at least 10 weeks.